Risk factors for fatigue severity in the post-COVID-19 condition: A prospective controlled cohort study of nonhospitalised adolescents and young adults - Joel Selvakumar; Lise Beier Havdal; Elias Myrstad Brodwall; Silke Sommen; Lise Lund Berven; Tonje Stiansen-Sonerud; Erin Cvejic; Vegard Bruun Bratholm Wyller (Brain, Behavior, & Immunity - Health)
Long COVID is a global health concern, leading to persistent symptoms and disability long after the acute SARS-CoV-2 infection in most age groups. The condition can manifest even following mild COVID-19, and in young people, it may have serious adverse consequences for educational attainment and transition to adulthood. Fatigue is the most prevalent symptom, but the underlying mechanisms remain poorly understood. In this prospective study of 404 SARS-CoV-2-positive and 105 SARS-CoV-2 negative, non-hospitalised youth (ages 12–25, female 62%), we investigated which factors in the early convalescent stage (<28 days since test) were associated with the severity of persistent fatigue at 6 months after infection. Participants completed questionnaires regarding clinical symptoms, social factors and psychological traits, and were subject to clinical and functional testing and biomarker analyses. Variables with significant (p < 0.2) associations to the outcome in simple linear regression were chosen for multivariable modelling, together with potential confounders. In the final multivariable model, SARS-CoV-2-positivity was a minor risk factor for fatigue severity at six months. Baseline severity of symptoms was the main risk factor and correlated with psychosocial factors such as loneliness and neuroticism, rather than biomarkers. Our results suggest that factors not related to infection are major risk factors for persistent fatigue in this age group.